Evaluation of salivary flow and drug interactions in patients with a diagnosis of diabetes mellitus - Kuroiwa, D. Noboru [UNESP]; Ruiz Da Cunha Melo, M. A. [UNESP]; Balducci, I. [UNESP]; Lodi, K. Bortolin [UNESP]; Alves, M. Ghislaine Oliveira [UNESP]; Almeida, J. Dias [UNESP] (My University, 2014)
Aim: Diabetes mellitus (DM) is one of the most common chronic diseases responsible for substantial loss on the quality of life in elderly. Oral manifestations in these patients include xerostomia and alterations in salivary flow and salivary pH. The aim of this study was to analyze the relationship between salivary flow, pH and medication. Methods: The sample consisted of 53 subjects aged 60 years and older, including 30 patients with a diagnosis of type 2 DM and 23 controls. Results: Salivary flow was 1.066±0.814 mL/min in the control group and 0.955±0.606 mL/min in the DM group, with no significant difference between groups (P=0.588). There was a significant difference (P=0.045) in mean salivary pH (DM: 5-267±0.828; control: 5.783±0.951). Only 32.07% of the patients reported to remove their denture while sleeping. Three of 53 subjects using medications presented severe drug interactions. Conclusion: In summary, dentists must be able to make the diagnosis, to recognize all factors related to salivary alterations in DM, and to prescribe adequate treatment related to oral condition. Patients with DM presented salivary pH below normal reference values. It is important to advice patients to remove their denture while sleeping in order to prevent traumatic irritations and infections with Candida albicans. Potentially harmful cases of drug interactions have to be observed in elderly patient. Further studies focusing on the nature of drug interactions as the cause of adverse events such as xerostomia and increased salivary pH are needed.
Keywords: Diabetes mellitus; Drug combinations; Saliva